Characterization of Some Olive Varieties Consumed without Pre-Treatment: Naturally Debittered Olives in Türkiye - Yaşar Mert Biçici; Yeşim Elmacı (Turkish Journal of Agriculture: Food Science and Technology)
In table olive production it is necessary to remove oleuropein by brine or dry salting method because it gives bitterness. However, some olive varieties such as Throuba Thassos-Greece, Djemali-Tunisia can be consumed without any de-bittering process. Some olives in Türkiye are also consumed without any pre-treatment and these are Kilis Yağlık, Butko, Hurma (Erkence cv.), and Nizip Yağlık olives. These naturally de-bittered olives were aimed to be characterized in this research. The lowest moisture content was determined for Kilis Yağlık (6.84%) and the highest moisture content was determined for Butko (50.01%). The oil and protein content of the samples was between, 16.66-68.46% and 0.19-18.13%, respectively. Total phenolic content (mg GAE/100g) of Kilis Yağlık, Butko, Hurma and Nizip Yağlık olive varieties were determined as 458.87, 152.09, 109.73, 234.33, respectively. The lowest antioxidant capacity was determined for Butko and the highest value was determined for Kilis Yağlık. The hardness values of the olives were found between 677.44-3688.06 (g). The L*, a*, b* values of olive samples were found between 26.14-32.05, 2.02-4.78, 2.37- 7.18, respectively. Highest oleic was determined for Hurma, highest linoleic acid was determined for Butko whereas the highest linolenic acid was determined for Nizip Yağlık. Volatile component analysis results of olives showed that 24, 23, 16 and 17 volatile components were detected in Kilis Yağlık, Butko, Hurma and Nizip Yağlık olives, respectively.